2015
DOI: 10.1097/yic.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 50 and 100 mg desvenlafaxine versus placebo on sexual function in patients with major depressive disorder

Abstract: The primary objective of this post-hoc analysis was to evaluate the effect of short-term treatment with desvenlafaxine versus placebo on sexual dysfunction (SD), assessed from Arizona Sexual Experiences Scale scores, in adult outpatients with major depressive disorder. Data from three randomized, double-blind, placebo-controlled trials of 50 or 100 mg/day desvenlafaxine for major depressive disorder were pooled. SD status, determined from Arizona Sexual Experiences Scale scores, was assessed at baseline and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…If an AD is required to have some serotoninergic effect and also to have a lower impact on sexual function and orgasm/ejaculation, fluvoxamine is the best candidate when not dosing above 100 mg/day [2]. Among drugs which are partially serotoninergic, the possibilities are desvenlafaxine (when dosing under 100 mg/day) [46] and vortioxetine (10–15 mg per day) [55]. A prospective naturalistic study of desvenlafaxine conducted by our Sexuality and Mental Health project group [56] showed promising results when prescribing this drug as the first AD to a group of depressed patients, with an incidence of TESD of 44.4% being observed.…”
Section: Results and Clinical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…If an AD is required to have some serotoninergic effect and also to have a lower impact on sexual function and orgasm/ejaculation, fluvoxamine is the best candidate when not dosing above 100 mg/day [2]. Among drugs which are partially serotoninergic, the possibilities are desvenlafaxine (when dosing under 100 mg/day) [46] and vortioxetine (10–15 mg per day) [55]. A prospective naturalistic study of desvenlafaxine conducted by our Sexuality and Mental Health project group [56] showed promising results when prescribing this drug as the first AD to a group of depressed patients, with an incidence of TESD of 44.4% being observed.…”
Section: Results and Clinical Approachmentioning
confidence: 99%
“…Desvenlafaxine [43], which has a smaller serotoninergic profile than venlafaxine, appears to cause less TESD at 50 mg, however TESD can appear at doses above 100 mg [46,70]. Recent observational data from a switching study in which inclusion and exclusion criteria were controlled showed that switching to desvenlafaxine led to a decrease of severe TESD from 93.3% to 75.6% [56] and an improvement of sexual desire and orgasmic dysfunction, but no improvement in sexual arousal.…”
Section: Results and Clinical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing information on the frequency of desvenlafaxine-associated SD comes from a post-hoc analysis of three double-blind and short-term clinical trials (two months) using the self-administered ASEX Scale in outpatients with depression using doses of 50–100 mg. The results indicate that SD rates were 54%, 47%, and 49% for 50 mg/day, 100 mg/day, and placebo, respectively, with adjusted odds ratios (95% confidence interval) vs. placebo of 1,205 (0.928, 1.564) and 1,129 (0.795, 1.604), respectively [54]. These results partially coincide with the SD figures found in our study with 44% of moderate/severe SD at three months in desvenlafaxine-naïve patients; however, the frequency was much higher (76%) in patients switched to desvenlafaxine due to previous AD-related sexual dysfunction after following the course for three months.…”
Section: Discussionmentioning
confidence: 99%
“…Naredna studija koja je ispitivala seksualnu disfunkciju kod pacijenata tretiranih velafaksinom bila je od iste grupe autora 2015. godine i rezultati te studije su ukazali da je veća doza • br. 1 leka povezana sa višom incidencom seksualnih disfunkcija odnosno da pacijenti koji uzimaju 100 mg desvenlafaksina imaju veći intenzitet seksualnih disfunkcija u odnosu na pacijente koji uzimaju 50 mg desvenlafaksina [11] .…”
Section: Seksualna Disfunkcijaunclassified